Gonad Maturity and Fecundity of Bluecheek Silver Grunt (Pomadasys argyreus) in Palabuhanratu Bay, West Java: Kematangan Gonad dan Fekunditas ikan gerot-gerot (Pomadasys argyreus) di Teluk Palabuhanratu, Jawa Barat - Mona Agatha; Yonvitner; Rahmat Kurnia (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2019)
A total of 806 fish samples were collected from the catch of local fishermen. The sex ratio of Pomadasys argyreus was 1:0,90. Four stages of gonadal development were observed in males and females, which dominated by stage I and II (immature). The highest gonadosomatic index (GSI) in males was 1,14 in September, while in females was 1,80 in May. Length at first maturity of Pomadasys argyreus was 140,12 mm for males and 135,01 mm for females. The highest value of condition factor was 1,05 for males and 1,10 for females. This fish spawn partially (partial spawner) and estimated spawns throughout the year with a spawning peak in June.